High Prevalence of Integrative and Conjugative Elements Encoding Transcription Activator-Like Effector Repeats in Mycoplasma hominis - Meygret, Alexandra; Peuchant, Olivia; Dordet-Frisoni, Emilie; Sirand-Pugnet, Pascal; Citti, Christine; Bébéar, Cécile; Béven, Laure; Pereyre, Sabine (Frontiers in Microbiology, 2019)
Integrative and conjugative elements (ICEs) are modular mobile genetic elements that can disseminate through excision, circularization, and transfer. Mycoplasma ICEs have recently been found distributed among some mycoplasma species and there is accumulating evidence that they play a pivotal role in horizontal gene transfers. The occurrence of ICEs has not been documented in Mycoplasma hominis, a human urogenital pathogen responsible for urogenital infections, neonatal infections and extragenital infections. In this study, we searched for, characterized, and compared ICEs by genome analyses of 12 strains of M. hominis. ICEs of 27-30 kbp were found in one or two copies in seven of the 12 M. hominis strains sequenced. Only five of these ICEs seemed to be functional, as assessed by detection of circular forms of extrachromosomal ICE were detected. Moreover, the prevalence of ICEs in M. hominis was estimated to be 45% in a collection of 120 clinical isolates of M. hominis, including 27 tetracycline-resistant tet(M)-positive isolates. The proportion of ICEs was not higher in isolates carrying the tet(M) gene, suggesting that ICEs are not involved in tetracycline resistance. Notably, all M. hominis ICEs had a very similar structure, consisting of a 4.0-5.1 kb novelunusual module composed of five to six juxtaposed CDSs. All the genes forming this module were specific to M. hominis ICEs as they had no homologues in other mycoplasma ICEs. In each M. hominis ICE, one to three CDSs encode proteins that share common structural features with transcription activator-like (TAL) effectors involved in polynucleotide recognition and signal transduction in symbiotic plant pathogen bacteria. The conserved and specific structure of M. hominis ICEs and the high prevalence in clinical strains suggest that these ICEs may confer a selective advantage for the physiology or pathogenicity of this human pathogenic bacterium. These data open the way for further studies aiming at unravelling horizontal gene transfers and virulence factors in M. hominis.